Characterization of Tulamoeba bucina n. sp., an Extremely Halotolerant Amoeboflagellate Heterolobosean Belonging to the Tulamoeba–Pleurostomum Clade (Tulamoebidae n. fam.). (13th October 2014) - Kirby, William A.; Tikhonenkov, Denis V.; Mylnikov, Alexandre P.; Janouškovec, Jan; Lax, Gordon; Simpson, Alastair G. B.
Abstract Most protozoans that have been cultivated recently from high salinity waters appear to be obligate halophiles. Phylogenetic analyses indicate that these species mostly represent independent lineages. Here, we report the cultivation, morphological characterization, and phylogenetic analysis of two strains (XLG1 and HLM‐8) of a new extremely halotolerant heterolobosean amoeboflagellate. This species is closely related to the obligate halophiles Tulamoeba peronaphora and Pleurostomum flabellatum, and more specifically to the former. Like Tulamoeba, the new species has a monopodial limax amoeba stage, however, its cyst stage lacks an intrusive pore plug. The flagellate stage bears a combination of a planar spiral feeding apparatus and unequal heterodynamic flagella that discriminates it from described Pleurostomum species. Strain XLG1 grows at salinities from 35‰ to 225‰. This degree of halotolerance is uncommon in protozoa, as most species showing growth in seawater are unable to grow at 200‰ salinity. The unrelatedness of most halophilic protozoa suggested that independent colonization of the hypersaline environment is more common than speciation within it. However, this study supports the idea that the Tulamoeba–Pleurostomum clade underwent an adaptive radiation within the hypersaline environment. A new species Tulamoeba bucina n. sp. is described, with Tulamoebidae n. fam. proposed for the Tulamoeba–Pleurostomum clade.